Effect of high intensity laser therapy on the range of motion of facial muscles in patients with Chronic Bell’s Palsy - Abdullatif, Hajer M. S.; Shaker, Hussein A. A.; Fahmy, Ebtesam M.; Mohamed, Rania R. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
Background: Bell’s palsy is a disease involving the seventh cranial nerve, which regulates facial muscle action. Facial muscles get paralyzed when this nerve is damaged. Objective: The primary objective of this researcher is to find out the effect of High Intensity Laser Therapy (HILT) on facial muscle function in patients with chronic bell’s palsy. Subjects and Methods: Twenty patients diagnosed with chronic Bell’s palsy and twenty healthy individuals of both sexes were recruited, falling within the age group of 20-40 years. Participants were assigned into two groups. Group A (Healthy individuals) and Group B (Bell’s palsy patients). Group A participants were intervened with Nd: YAG High intensity LASER, one session/week for total of 4 sessions. Facial angle measurement was done in resting state and in contracted positions of the respective muscles on both the sides of face. These angles were analyzed using the Auto-CAD program. Results: A significant increase in facial angle was observed in raising eye brow, light eye closing, smiling, kissing, and blowing on the non-affected side and a significant decrease of these angles on the affected side following treatment (p<0.05). Comparison between non-affected sides versus affected side showed significant differences in measured angles except for smiling and kissing angles. Conclusion: High-Intensity Laser Therapy (HILT) improved the function of the facial muscles in patients with chronic Bell’s palsy.